Bimetal monatomic photo-Fenton catalyst, preparation, sewage degradation method and application
By loading Mo-Fe bimetallic single atoms on two-dimensional carbon nitride nanosheets, regulating the spin state of Fe, bimetallic single atom photofenton catalyst was prepared, which solved the problem of insufficient activity of single atom catalysts, and achieved efficient organic wastewater degradation and good cycle stability.
Patent Information
- Application Number
- CN202411452473.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-04-04
AI Technical Summary
Existing single-atom catalysts are not active and selective when catalyzing complex reactions. Understanding the synthesis and synergistic effects of diatom catalysts still has challenges, and it is difficult to develop high-activity and high-stability bimetallic catalysts.
Two-dimensional carbon nitride nanosheets are used as support to support Mo-Fe bimetallic single atoms, and bimetallic single atom photofenton catalyst is prepared by regulating the spin state of Fe, and its catalytic activity and selectivity are improved through specific preparation methods and structural design.
It achieves better catalytic activity and selectivity than single atomic catalysts, has high spin state, strong adsorption performance and a wide range of pH applications, and can efficiently degrade organic wastewater under light conditions, and maintain a degradation rate of more than 90% after recycling.
Smart Images

Figure CN119746900A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a bimetallic single-atom photo-Fenton catalyst, a preparation method and a sewage degradation method and application thereof. Background Art
[0002] Single-atom catalysts (SACs) have attracted great attention in the field of heterogeneous catalysis. Due to the maximum atomic utilization of the metal center, the unique electronic structure and the unsaturated coordination environment, SAC catalysts exhibit high activity and selectivity in electrocatalytic reactions. However, due to the inherent electronic structure and the single active metal atom, SACs are generally able to catalyze basic reactions of single molecules and are not suitable for complex reactions involving the synergistic activation of multiple molecules and intermediates. Compared with single-atom catalysts, diatomic catalysts (DACs) have great potential in improving the intrinsic activity of catalysts and are an effective way to improve catalytic activity. However, the development of DACs is still in its infancy. The synthesis of existing DACs and the understanding of the synergistic effects of two sets of single-atom sites at the atomic level remain challenges. It is of great significance to develop diatomic catalysts with high activity and high stability. Summary of the invention
[0003] The main purpose of the present invention is to provide a bimetallic single-atom photo-Fenton catalyst, a method for preparing and degrading sewage, and an application thereof. The bimetallic single-atom photo-Fenton catalyst in the present invention has an excellent photo-Fenton degradation effect, high activity, strong selectivity, and stable performance, and exhibits better catalytic activity and catalytic selectivity than single-atom catalysts.
[0004] In order to achieve the above objectives, the present invention provides the following technical solutions.
[0005] In a first aspect of the present invention, a bimetallic single-atom photo-Fenton catalyst is provided, the organizational structure of which includes carbon nitride two-dimensional nanosheets and Mo-Fe bimetallic single atoms loaded on the carbon nitride two-dimensional nanosheets.
[0006] In some embodiments of the present invention, the specific surface area of the carbon nitride two-dimensional nanosheet is 300 m 2 / g~800m 2 / g.
[0007] In some embodiments of the present invention, in the Mo-Fe bimetallic single atom, the average distance between the Mo atom and the Fe atom is 2.85 angstroms to 2.87 angstroms.
[0008] The second aspect of the present invention provides a method for preparing the bimetallic single-atom photo-Fenton catalyst described in the first aspect, characterized in that the preparation method comprises the following steps: preparing a precursor cyanuric acid-melamine-triethylenetetramine powder; respectively adding an alcohol solution containing molybdenum ions and an alcohol solution containing iron ions to the precursor cyanuric acid-melamine-triethylenetetramine powder, and grinding to obtain a powder mixture; calcining and cooling the powder mixture under a protective atmosphere to obtain the bimetallic single-atom photo-Fenton catalyst.
[0009] In some embodiments of the present invention, the mass percentage of cyanuric acid in the precursor cyanuric acid-melamine-triethylenetetramine powder is 40% to 50%, the mass percentage of melamine is 40% to 50%, and the balance is triethylenetetramine.
[0010] In some embodiments of the present invention, the mass percentage of molybdenum ions in the powder mixture is 10% to 35%, the mass percentage of iron ions is 10% to 35%, and the mass percentage of the precursor cyanuric acid-melamine-triethylenetetramine powder is 30% to 80%.
[0011] In some embodiments of the present invention, the calcination conditions include: heating to 400° C. to 600° C. under a protective atmosphere and maintaining the temperature for 0.5 h to 4 h.
[0012] In some embodiments of the present invention, the heating rate of the calcination process is 1° C. / min to 5° C. / min.
[0013] In some embodiments of the present invention, the preparation of the precursor cyanuric acid-melamine-triethylenetetramine powder includes: adding a triethylenetetramine aqueous solution to a cyanuric acid solution to obtain a mixed solution; adding a melamine suspension to the mixed solution to form a white milky colloid; and subjecting the white milky colloid to ultrasonic treatment, shaking, filtering, drying, and grinding.
[0014] The third aspect of the present invention provides an application of the bimetallic single-atom photo-Fenton catalyst described in the first aspect or the bimetallic single-atom photo-Fenton catalyst prepared by the preparation method described in the second aspect in organic wastewater treatment.
[0015] In a fourth aspect, the present invention provides a method for degrading organic wastewater using the bimetallic single-atom photo-Fenton catalyst described in the first aspect or the bimetallic single-atom photo-Fenton catalyst prepared by the preparation method described in the second aspect. The method for degrading organic wastewater comprises: mixing the bimetallic single-atom photo-Fenton catalyst and peroxide into the wastewater to be degraded, adjusting the pH with hydrochloric acid or sodium hydroxide solution, and degrading the wastewater under light conditions.
[0016] Compared with the prior art, the present invention achieves the following technical effects:
[0017] The bimetallic single-atom photo-Fenton catalyst provided by the present invention has an excellent photo-Fenton degradation effect, high activity, strong selectivity, and stable performance, and exhibits better catalytic activity and catalytic selectivity than single-atom catalysts.
[0018] The Mo-Fe bimetallic single-atom photo-Fenton catalyst provided by the present invention has a thinner two-dimensional structure, which is more conducive to the mass transfer process than the existing three-dimensional structure photo-Fenton catalyst.
[0019] The Mo-Fe bimetallic single atom photo-Fenton catalyst provided by the present invention has a high spin state, and has stronger adsorption performance and catalytic performance compared with a single Fe atom with a low spin state.
[0020] The Mo-Fe bimetallic single-atom photo-Fenton catalyst provided by the present invention has a wider pH application range than traditional Fenton catalysts.
[0021] The raw materials for the preparation of the invention are widely available and low in price; the preparation method has no environmental pollution; the synthesis operation is simple and the preparation is suitable for large-scale preparation and application.
[0022] The Mo-Fe bimetallic single-atom photo-Fenton catalyst provided by the present invention has a pollutant degradation rate of more than 95% within 1 hour of photocatalysis, and after being recycled for 5 times, the pollutant degradation rate is still more than 90%.
[0023] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings:
[0025] Figure 1 Electron microscope images of Mo-Fe bimetallic single-atom photo-Fenton catalysts prepared according to some embodiments of the present invention; wherein a) is a scanning electron microscope image; b) is a transmission electron microscope image; c) is a spherical aberration electron microscope image;
[0026] Figure 2 for Figure 1 c The distance diagram between Mo atoms and Fe atoms corresponding to positions 1-3;
[0027] Figure 3 This is a diagram showing the effect of the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 of the present invention on the degradation of bisphenol A under different pH conditions;
[0028] Figure 4 The Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 of the present invention is a graph showing the degradation effect of bisphenol A (BPA) in different systems;
[0029] Figure 5 This is a graph showing the degradation effects of the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 of the present invention on bisphenol A (BPA), sulfamethoxazole (SMX), meropenem (MEM), ciprofloxacin (CIP) and carbamazepine (CBZ);
[0030] Figure 6 This is a diagram showing the cyclic degradation effect of the Mo-Fe bimetallic single-atom photo-Fenton catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0033] In the description of the embodiments of the present invention, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0034] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0035] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this document generally indicates that the associated objects before and after are in an "or" relationship.
[0036] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0037] The Fenton oxidation method based on hydroxyl radical (·OH) has been widely studied for the removal of refractory organic pollutants because ·OH has a high redox potential (E0=2.73V) and strong electrophilic addition properties. In addition, the heterogeneous Fenton reaction has the advantages of easy separation of catalysts, reduced metal leaching, and environmental compatibility, overcoming the defects of traditional homogeneous Fenton technology. However, heterogeneous Fenton-like reactions are still limited by the low activation efficiency of H2O2 and the high consumption of H2O2, which limits its application in environmental remediation. Generally speaking, in Fenton-like reactions, H2O2 is activated to form ·OH mainly by M n + / M (n+1)+ Metal-pair catalysis (where M represents a transition metal atom), the rate-limiting step is M (n+1)+ Restore to M n+ Light-enhanced heterogeneous Fenton (photo-Fenton) can enhance the synthesis of low-valent M through the synergistic effect of photocatalytic technology and Fenton-like reactions. n+ The photo-Fenton mechanism includes: (1) the catalyst captures light energy to generate photogenerated electrons, which promote the activation of low-valent M n+ (2) By optimizing the separation of electron-hole pairs, photogenerated electrons are effectively consumed, holes with strong oxidative ability are released, and photocatalytic oxidation is promoted. Due to its inherent synergistic steps, the photo-Fenton process can improve the degradation rate and mineralization rate of difficult-to-degrade pollutants.
[0038] The present invention provides a bimetallic single atom photo-Fenton catalyst, see Figure 1 As shown, the organizational structure of the bimetallic single atom photo-Fenton catalyst includes carbon nitride two-dimensional nanosheets and Mo-Fe bimetallic single atoms supported on the carbon nitride two-dimensional nanosheets. The bimetallic single atom photo-Fenton catalyst of the present invention has an excellent photo-Fenton degradation effect, high activity, strong selectivity, stable performance, and exhibits better catalytic activity and catalytic selectivity than single atom catalysts.
[0039] The bimetallic single atom photo-Fenton catalyst of the present invention has a porous layered structure, which can be seen in Figure 1 a and Figure 1 b, which is conducive to providing a larger specific surface area and more reactive sites. In an embodiment of the invention, the specific surface area of the carbon nitride two-dimensional nanosheet is 300 m 2 / g~800m 2 / g. For example, the specific surface area of the carbon nitride two-dimensional nanosheet can be 300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g or any value satisfying the above range.
[0040] In the embodiment of the invention, in the Mo-Fe bimetallic single atom, the average distance between the Mo atom and the Fe atom is 2.85 angstroms to 2.87 angstroms, see Figure 1 c and Figure 2 shown.
[0041] The present invention provides a method for preparing a bimetallic single atom photo-Fenton catalyst. The key lies in controlling the spin of Fe atoms by Mo atoms to achieve spin control, thereby greatly improving the catalytic activity of Mo and Fe bimetallic single atoms.
[0042] The preparation method of the bimetallic single-atom photo-Fenton catalyst in the present invention is carried out according to the following steps.
[0043] (1) Prepare precursor cyanuric acid-melamine-triethylenetetramine powder.
[0044] In the embodiment of the present invention, the precursor cyanuric acid-melamine-triethylenetetramine powder is prepared by using cyanuric acid, melamine, triethylenetetramine aqueous solution.
[0045] In some embodiments of the present invention, a triethylenetetramine aqueous solution is added to a cyanuric acid solution to obtain a mixed solution; a melamine suspension is added to the mixed solution to form a white milky colloid; the white milky colloid is subjected to ultrasonic treatment, as well as oscillation, suction filtration, drying, and grinding to obtain a precursor cyanuric acid-melamine-triethylenetetramine powder.
[0046] In some embodiments of the present invention, cyanuric acid and deionized water are ultrasonically dispersed in a conical flask to obtain a cyanuric acid solution, and then an aqueous solution of triethylenetetramine is added to the cyanuric acid solution and dissolved to obtain a mixed solution.
[0047] In some embodiments of the present invention, melamine is added to deionized water and subjected to ultrasonic treatment to form a suspension, and the melamine suspension is added to the above-mentioned cyanuric acid and solution to obtain a white emulsion colloidal polymer.
[0048] In some embodiments of the present invention, 0.1g to 1.0g (1mmol to 8mmol) of cyanuric acid and 5mL to 20mL of deionized water are ultrasonically dispersed in a conical flask to obtain a cyanuric acid dispersion; then 0.15g to 1.5g (1mmol to 10mmol) of triethylenetetramine aqueous solution is added to the cyanuric acid dispersion and dissolved to obtain a mixed solution. Then 0.06g to 0.64g (1mmol to 5mmol) of melamine is added to 5mL to 20mL of deionized water and ultrasonically rinsed to form a suspension, and the melamine suspension is added to the above mixed solution to immediately form a white milky colloid. After ultrasonicating the white milky colloid for at least 10 minutes, it is shaken at room temperature for 0.5h to 4h, then filtered, dried, and ground to obtain a precursor cyanuric acid-melamine-triethylenetetramine powder.
[0049] Exemplarily, the amount of cyanuric acid can be one of 1mmol, 2mmol, 3mmol, 4mmol, 5mmol, 6mmol, 7mmol, 8mmol or any value satisfying the above range. The amount of triethylenetetramine can be one of 1mmol, 2mmol, 3mmol, 4mmol, 5mmol, 6mmol, 7mmol, 8mmol, 9mmol, 10mmol or any value satisfying the above range. The amount of melamine can be one of 1mmol, 2mmol, 3mmol, 4mmol, 5mmol or any value satisfying the above range.
[0050] It is worth mentioning that room temperature means the temperature is between 20℃ and 30℃.
[0051] In some embodiments of the present invention, the mass percentage of cyanuric acid in the precursor cyanuric acid-melamine-triethylenetetramine powder is 40% to 50%, the mass percentage of melamine is 40% to 50%, and the balance is triethylenetetramine. In other words, the mass percentages of cyanuric acid, melamine and triethylenetetramine in the precursor cyanuric acid-melamine-triethylenetetramine powder are 40% to 50%: 40% to 50%: 0 to 10% and are not 0.
[0052] Exemplarily, the mass percentage of cyanuric acid in the precursor cyanuric acid-melamine-triethylenetetramine powder is 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or any value satisfying the above range. The mass percentage of melamine in the precursor cyanuric acid-melamine-triethylenetetramine powder is 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or any value satisfying the above range. The mass percentage of triethylenetetramine in the precursor cyanuric acid-melamine-triethylenetetramine powder is one of 0.1%, 0.2%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value satisfying the above range.
[0053] (2) Adding an alcohol solution containing molybdenum ions and an alcohol solution containing iron ions dropwise into a precursor cyanuric acid-melamine-triethylenetetramine powder, respectively, and grinding to obtain a powder mixture.
[0054] In the implementation of the present invention, the alcohol solvent in the alcohol solution containing molybdenum ions can be ethanol, and the alcohol solvent in the alcohol solution containing iron ions can be ethanol.
[0055] In some embodiments of the present invention, the alcohol solution containing molybdenum ions can be an alcohol solution of molybdenum pentachloride (MoCl5).
[0056] In some embodiments of the present invention, the alcohol solution containing iron ions may be an alcohol solution of ferric chloride hexahydrate (FeCl 3 ·6H 2 O).
[0057] In some embodiments of the present invention, the amount of the substance of the molybdenum ion in the alcohol solution containing molybdenum ions may be 1 mmol to 5 mmol. Exemplarily, the amount of the substance of the molybdenum ion in the alcohol solution containing molybdenum ions may be one of 1 mmol, 2 mmol, 3 mmol, 4 mmol, 5 mmol or any value satisfying the above range.
[0058] In some embodiments of the present invention, the amount of the substance of the iron ion in the alcohol solution containing the iron ion may be 1 mmol to 5 mmol. Exemplarily, the amount of the substance of the iron ion in the alcohol solution containing the iron ion may be one of 1 mmol, 2 mmol, 3 mmol, 4 mmol, 5 mmol or any value satisfying the above range.
[0059] In some embodiments of the present invention, the molar ratio of platinum ions to iron ions is 1:1.
[0060] In some embodiments of the present invention, MoCl5 and FeCl3·6H2O are weighed in a preset ratio and dissolved in an alcohol solvent. For example, 0.27 g to 1.36 g (1 mmol to 5 mmol) of MoCl5 and 0.27 g to 1.35 g (1 mmol to 5 mmol) of FeCl3·6H2O are weighed and dissolved in 1 mL to 10 mL of ethanol, respectively, and then the ethanol solution of MoCl5 and the ethanol solution of FeCl3·6H2O are added dropwise to 1.0 g to 5.0 g of precursor cyanuric acid-melamine-triethylenetetramine powder, respectively, and ground evenly.
[0061] In some embodiments of the present invention, the mass ratio of MoCl5, FeCl3·6H2O to the cyanuric acid-melamine-triethylenetetramine powder is 0.54-2.7:0.54-2.7:0.5-2.5.
[0062] In some embodiments of the present invention, the molar ratio of MoCl5 to FeCl3·6H2O is 1:1.
[0063] In some embodiments of the present invention, the mass percentage of platinum ions in the powder mixture is 10% to 35%, the mass percentage of iron ions is 10% to 35%, and the mass percentage of precursor cyanuric acid-melamine-triethylenetetramine powder is 30% to 80%. Exemplarily, the mass percentage of platinum ions in the powder mixture can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or any value that meets the above range value. The mass percentage of iron ions in the powder mixture can be one of 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, or any numerical value that meets the above range value. The mass percentage of precursor cyanuric acid-melamine-triethylenetetramine powder in the powder mixture can be one of 30%, 40%, 50%, 60%, 70%, 80%, or any numerical value that meets the above range value.
[0064] (3) The powder mixture is calcined and cooled under a protective atmosphere to obtain a bimetallic single-atom photo-Fenton catalyst.
[0065] In an embodiment of the present invention, the calcination conditions include: heating to 400°C to 600°C under a protective atmosphere and maintaining for 0.5h to 4h. For example, the calcination temperature may be one of 400°C, 450°C, 500°C, 550°C, 600°C, or any value satisfying the above range. The calcination time may be one of 0.5h, 1h, 1.5h, 2h, 3.5h, 4h, or any value satisfying the above range.
[0066] In the embodiment of the present invention, the protective atmosphere may be, but is not limited to, a nitrogen atmosphere.
[0067] In an embodiment of the present invention, the heating rate of the calcination process is 1°C / min to 5°C / min. For example, the heating rate may be one of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or any value satisfying the above range.
[0068] In some embodiments of the present invention, the powder mixture is placed in a tubular furnace, heated to 400°C to 550°C at a heating rate of 1°C / min to 5°C / min under a nitrogen atmosphere, calcined for 0.5h to 4h, and taken out after cooling to room temperature to obtain a Mo-Fe bimetallic single-atom photo-Fenton catalyst.
[0069] The bimetallic single-atom photo-Fenton catalyst provided by the present invention improves the performance of catalyzing the photo-Fenton reaction by regulating the spin state of Fe, and can be applied to the treatment of organic wastewater.
[0070] The method for degrading organic wastewater using a bimetallic monatomic photo-Fenton catalyst provided by the present invention comprises: mixing a bimetallic monatomic photo-Fenton catalyst and a peroxide (such as hydrogen peroxide) into wastewater to be degraded, adjusting the pH using hydrochloric acid or sodium hydroxide solution, and performing a degradation reaction under light conditions.
[0071] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0072] Example 1
[0073] Disclosed are a Mo-Fe bimetallic single-atom photo-Fenton catalyst and a preparation method thereof. The preparation method of the Mo-Fe bimetallic single-atom photo-Fenton catalyst is as follows:
[0074] (1) Weigh 0.52 g (4 mmol) of cyanuric acid and 20 mL of deionized water, add them to a conical flask and perform ultrasonic dispersion to obtain a cyanuric acid dispersion; then add 0.75 g (5 mmol) of triethylenetetramine aqueous solution (5 mL) to the cyanuric acid dispersion to dissolve it and obtain a mixed solution. Then add 0.32 g (2.5 mmol) of melamine to 20 mL of deionized water and use ultrasonic washing to form a melamine suspension. The melamine suspension is added to the above mixed solution to immediately form a white milky colloid. The colloid is ultrasonically treated for 10 minutes, shaken at room temperature for 4 hours, then filtered, dried, and ground to obtain a precursor cyanuric acid-melamine-triethylenetetramine powder.
[0075] (2) 0.54 g of MoCl5 and 0.54 g of FeCl3·6H2O were weighed in a molar ratio of 1:1 and dissolved in 5 mL of ethanol respectively. The prepared MoCl5 ethanol solution and FeCl3·6H2O ethanol solution were then added dropwise to 1.25 g of the precursor cyanuric acid-melamine-triethylenetetramine powder prepared in step (1), and ground evenly to obtain a powder mixture.
[0076] (3) The powder mixture obtained in step (2) is placed in a tubular furnace, heated to 550° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, calcined at 550° C. for 2 h, and taken out after cooling to room temperature to obtain a Mo-Fe bimetallic single-atom photo-Fenton catalyst.
[0077] Figure 1 a and Figure 1 b shows the scanning electron microscope image and transmission electron microscope image of the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1, respectively. It can be seen from the figure that the prepared Mo-Fe bimetallic single atom photo-Fenton catalyst forms a porous layered structure, which is conducive to providing a larger specific surface area and more reactive sites. Figure 1 c and Figure 2 As shown in the figure, the organizational structure of the Mo-Fe bimetallic single atom photo-Fenton catalyst includes carbon nitride two-dimensional nanosheets and Mo-Fe bimetallic single atoms supported on the carbon nitride two-dimensional nanosheets. The specific surface area of the carbon nitride two-dimensional nanosheets in the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 is 480 m 2 / g, the average distance between Mo atoms and Fe atoms is 2.85 angstroms to 2.87 angstroms.
[0078] In the test, antibiotics, such as bisphenol A (BPA), are added to the water to simulate pollutant wastewater.
[0079] The effect of pH value on the degradation efficiency of bisphenol A by the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 was tested. The specific test steps are as follows:
[0080] (1) In a 100 mL beaker, add 30 mL of bisphenol A (20 mg / L -1 ) and 6 mg Mo-Fe bimetallic single atom photo-Fenton catalyst.
[0081] (2) Place in the dark and stir magnetically for 60 min to reach adsorption-desorption equilibrium to obtain a suspension as the initial solution.
[0082] (3) The initial pH values of the above-mentioned initial solutions were adjusted to 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, and 11.0 respectively using hydrochloric acid or sodium hydroxide solution, and 300 μL of H2O2 was added thereto respectively. The initial pH values of the above-mentioned initial solutions were adjusted to 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, and 11.0 respectively. The initial pH values of the initial solutions were adjusted to 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, and 11.0 respectively using hydrochloric acid or sodium hydroxide solution, and 300 μL of H2O2 was added thereto respectively. The initial pH values of the initial solutions were adjusted to -2 ) to undergo degradation reaction. At regular intervals, 500 μL of sample solution was taken and filtered through a 0.22 μm polytetrafluoroethylene filter membrane, and the concentration of bisphenol A was determined by high performance liquid chromatography.
[0083] The Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 has a degradation efficiency of bisphenol A under different pH conditions. Figure 3 shown.
[0084] Depend on Figure 3 It can be found that when the initial pH value of the initial solution increases from 3.0 to 11.0, the degradation efficiency of the Mo-Fe bimetallic single atom photo-Fenton catalyst for bisphenol A shows a trend of first increasing and then decreasing. When the initial pH value of the initial solution is 7.0 and 11.0, after 60 minutes of photoreaction, bisphenol A shows the highest and lowest removal rates, which are about 99% and 85%, respectively. This shows that in a wide pH range, the Mo-Fe bimetallic single atom photo-Fenton catalyst has efficient photo-Fenton degradation activity for bisphenol A, and acidic conditions are most favorable.
[0085] The photo-Fenton degradation effect of the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 on bisphenol A was tested under different systems. The specific test steps are as follows:
[0086] (1) In a 100 mL beaker, add 30 mL of bisphenol A (20 mg / L -1 ) and 6 mg Mo-Fe bimetallic single atom photo-Fenton catalyst.
[0087] (2) Place in the dark and stir magnetically for 60 min to reach adsorption-desorption equilibrium to obtain a suspension as the initial solution.
[0088] (3) The initial pH values of the above-mentioned initial solutions were adjusted to 7.0 by hydrochloric acid or sodium hydroxide solution, and were marked as systems 1-4. System 1 was used as a blank test; 300 μL H2O2 was added to system 2 and system 3; system 3 and system 4 were respectively exposed to visible light (wavelength λ>420nm, light intensity 20mw·cm -2 ) to perform degradation reaction. At the same time, degradation reaction was performed in dark conditions on system 1 and system 2. At regular intervals, 500 μL of sample solution was taken, filtered through a 0.22 μm polytetrafluoroethylene filter membrane, and the concentration of bisphenol A was determined by high performance liquid chromatography.
[0089] Figure 4 The degradation efficiency of bisphenol A (BPA) by the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 under different systems. The Mo-Fe bimetallic single atom photo-Fenton catalyst can promote the decomposition of hydrogen peroxide to produce hydroxyl radicals and superoxide radicals under visible light irradiation, which can be used to degrade organic pollutants in water. Figure 4 It can be seen that under the conditions of hydrogen peroxide (H2O2) and light (visible light Vis), the Mo-Fe bimetallic single atom photo-Fenton catalyst has the best degradation activity. After 60 minutes of photoreaction, the removal rate of bisphenol A reaches 99%.
[0090] The Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 was tested for its applicability to photo-Fenton degradation of different antibiotics. Among them, the antibiotics include bisphenol A, sulfamethoxazole, meropenem, ciprofloxacin, carbamazepine, etc. The specific experimental steps are as follows:
[0091] (1) Add 30 mL of bisphenol A (BPA, 20 mg / L) to each of the five 100 mL beakers labeled 1-5. -1 ), sulfamethoxazole (SMX, 20 mg·L -1 ), meropenem (MEM, 20 mg·L -1 ), ciprofloxacin (CIP, 20 mg·L -1 ), carbamazepine (CBZ, 20 mg·L -1 ), and 6 mg Mo-Fe bimetallic single atom photo-Fenton catalyst was added respectively.
[0092] (2) Place in the dark and stir magnetically for 60 min to reach adsorption-desorption equilibrium, and obtain 5 groups of initial solutions 1-5.
[0093] (3) Add 300 μL H2O2 to each of the five initial solutions 1-5 and observe the reaction under visible light (wavelength λ>420 nm, light intensity 20 mw·cm -2) to undergo degradation reaction. At regular intervals, 500 μL of sample solution was taken and filtered through a 0.22 μm polytetrafluoroethylene filter membrane, and the concentration of each antibiotic was determined by high performance liquid chromatography.
[0094] Figure 5 The activity diagram of the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 for photo-Fenton degradation of different antibiotics is shown. Figure 5 It can be found that after the photo-Fenton reaction, the degradation rates of BPA, SMX, MEM, CIP and CBZ can reach about 99% (60min), 99% (40min), 99% (50min), 99% (50min) and 99% (50min), respectively, with good removal effects. This shows that the Mo-Fe bimetallic single atom photo-Fenton catalyst has universal applicability for the photo-Fenton catalytic degradation of antibiotic pollutants.
[0095] The cyclic degradation effect of the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 on bisphenol A was tested. The specific test operation is as follows:
[0096] (1) In a 100 mL beaker, add 30 mL of bisphenol A (20 mg / L -1 ) and 6 mg Mo-Fe bimetallic single atom photo-Fenton catalyst.
[0097] (2) Place in the dark and stir magnetically for 60 min to reach adsorption-desorption equilibrium to obtain the initial solution.
[0098] (3) Add 300 μL H2O2 to the initial solution and illuminate it under visible light (wavelength λ>420 nm, light intensity 20 mw cm -2 ) to undergo degradation reaction. At regular intervals, 500 μL of sample solution was taken and filtered through a 0.22 μm polytetrafluoroethylene filter membrane, and the concentration of bisphenol A was determined by high performance liquid chromatography.
[0099] (4) After the photo-Fenton degradation reaction is completed, the residual Mo-Fe bimetallic single atom photo-Fenton catalyst is filtered through a 0.22 μm polytetrafluoroethylene filter membrane, washed, and dried.
[0100] (5) The catalyst obtained after drying in step (4) is reused, and steps (1) to (4) are repeated to perform 5 consecutive cycle tests.
[0101] Figure 6 The activity diagram of the Mo-Fe bimetallic single atom photo-Fenton catalyst prepared in Example 1 for photo-Fenton cycle catalytic degradation of bisphenol A. Figure 6 It can be seen that after 5 cycles of reaction, the removal rate of bisphenol A is still 94%, achieving good reusability.
[0102] The bimetallic single-atom photo-Fenton catalyst provided by the present invention has a pollutant degradation rate of more than 95% within 1 hour of photocatalysis, and after being recycled for 5 times, the pollutant degradation rate is still more than 90%.
[0103] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A bimetallic single-atom photo-Fenton catalyst, characterized in that: The organizational structure of the catalyst includes carbon nitride two-dimensional nanosheets and Mo-Fe bimetallic single atoms supported on the carbon nitride two-dimensional nanosheets.
2. The bimetallic single-atom photo-Fenton catalyst according to claim 1, characterized in that: The specific surface area of the carbon nitride two-dimensional nanosheet is 300 m 2 / g~800m 2 / g.
3. The bimetallic single-atom photo-Fenton catalyst according to claim 1, characterized in that: In the Mo-Fe bimetallic single atom, the average distance between the Mo atom and the Fe atom is 2.85 angstroms to 2.87 angstroms.
4. A method for preparing the bimetallic single-atom photo-Fenton catalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: preparing precursor cyanuric acid-melamine-triethylenetetramine powder; The alcohol solution containing molybdenum ions and the alcohol solution containing iron ions are respectively added dropwise to the precursor cyanuric acid-melamine-triethylenetetramine powder, and ground to obtain a powder mixture; The powder mixture is calcined and cooled under a protective atmosphere to obtain the bimetallic single-atom photo-Fenton catalyst.
5. The preparation method according to claim 4, characterized in that: The precursor cyanuric acid-melamine-triethylenetetramine powder has a mass percentage of 40% to 50% of cyanuric acid, a mass percentage of melamine of 40% to 50%, and the balance of triethylenetetramine.
6. The preparation method according to claim 4, characterized in that: The mass percentage of molybdenum ions in the powder mixture is 10% to 35%, the mass percentage of iron ions is 10% to 35%, and the mass percentage of the precursor cyanuric acid-melamine-triethylenetetramine powder is 30% to 80%.
7. The preparation method according to claim 4, characterized in that: The calcination conditions include: heating to 400°C to 600°C under a protective atmosphere and maintaining for 0.5h to 4h; Preferably, the heating rate of the calcination process is 1°C / min to 5°C / min.
8. The preparation method according to claim 4 or 5, characterized in that: The preparation of the precursor cyanuric acid-melamine-triethylenetetramine powder comprises: adding the triethylenetetramine aqueous solution into the cyanuric acid solution to obtain a mixed solution; adding melamine suspension into the mixed solution to form a white milky colloid; The white milky colloid is subjected to ultrasonic treatment, shaking, suction filtration, drying and grinding.
9. Use of the bimetallic single-atom photo-Fenton catalyst described in any one of claims 1 to 3 or the bimetallic single-atom photo-Fenton catalyst prepared by the preparation method described in any one of claims 4 to 8 in organic wastewater treatment.
10. A method for degrading organic wastewater using the bimetallic single-atom photo-Fenton catalyst described in any one of 1 to 3 or the bimetallic single-atom photo-Fenton catalyst prepared by the preparation method described in any one of claims 4 to 8, characterized in that: include: The bimetallic single atom photo-Fenton catalyst and peroxide are mixed into the wastewater to be degraded, the pH is adjusted with hydrochloric acid or sodium hydroxide solution, and the wastewater is degraded under light conditions.